Speaking for Islam : religious authorities in Muslim societies - Krämer, Gudrun.; Schmidtke, Sabine. (Social, Economic and Political Studies of the Middle East and Asia, 2006)
Who speaks for Islam? To whom do Muslims turn when they look for guidance? To what extent do individual scholars and preachers exert religious authority, and how can it be assessed? The upsurge of Islamism has lent new urgency to these questions, but they have deeper roots and a much longer history, and they certainly should not be considered in the light of present concerns only. The present volume - grown out of an international symposium at the Free University, Berlin in 2002 - is not so much concerned with religious authority , but with religious authorities , men and women claiming, projecting and exerting religious authority within a given context. It addresses issues such as the relationship of knowledge, conduct and charisma, the social functions of the schools of law and theology, and the efforts on the part of governments and rulers to organize religious scholars and to implement state-centred hierarchies. The volume focuses on Middle Eastern Muslim majority societies in the period from the eighteenth to the twentieth centuries, and the individual papers offer case studies elucidating important aspects of the wider phenomenon. Individually and collectively, they highlight the scope and variety of religious authorities in past and present Muslim societies. This book is also available in paperback .